Heavy-ion acceleration and self-generated waves in coronal shocks - Battarbee M; Laitinen T; Vainio R (EDP SCIENCES S A, 2022)
Conclusions. We suggest that understanding the acceleration of minor ions at coronal shocks requires simulations which allow us to explore trapping dynamics and acceleration timescales in detail, including evolution of the turbulent trapping boundary. We conclude that steady-state models do not adequately describe the acceleration of heavy ions in coronal shocks.